Dampak positive reinforcement terhadap kemandirian anak - Nurul Istiqomah , Fitrah; Nur Zuama, Shofiyanti; Imamah, Zakiyyatul; Agusniatih, Andi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2025)
The low level of children's independence is the background of this study. To increase independence, a positive reinforcement strategy is applied as a method of forming consistent positive behavior and character. The purpose of this study was to determine the effect of positive reinforcement on the independence of early childhood. This study uses a quantitative approach with an experimental method. The subjects consisted of 16 children, namely 9 girls and 7 boys in the odd semester of the 2024/2025 academic year. Data processing was carried out using the Paired Sample T Test analysis which was carried out with the help of the SPSS Statistics IMB program. The results of the research findings, there is a significance value of .000, because the significance value of the T-Test <0.05 (.000 <0.05), then Ha is accepted and Ho is rejected. In addition, there was an increase in the level of children's independence after being given treatment, which was seen from three aspects observed. In the initiative aspect, such as tidying up stationery by giving it a star symbol, there was an increase in the category (BSB) from 0% to 31%, category (BSH) from 19% to 31%, while category (MB) decreased from 56% to 38%, and category (BB) decreased from 25% to 0%. In the aspect of responsibility observed through the approach to children, the BSB category increased from 0% to 31%, BSH from 25% to 38%, and MB decreased from 75% to 31%. While in the aspect of self-control which was strengthened through giving praise, the BSB category increased from 0% to 25%. roviding various positive reinforcements that vary makes children feel appreciated so that it can attract children's attention to carry out independent actions continuously.